Serum albumin predicts survival in patients with hilar cholangiocarcinoma. (6th July 2016) - Waghray, Abhijeet; Sobotka, Anastasia; Marrero, Carlos Romero; Estfan, Bassam; Aucejo, Federico; Narayanan Menon, KV
Abstract : Background and aims: Hilar cholangiocarcinoma is a devastating malignancy with incidence varying by geography and other risk factors. Rapid progression of disease and delays in diagnosis restrict the number of patients eligible for curative therapy. The objective of this study was to determine prognostic factors of overall survival in all patients presenting with hilar cholangiocarcinoma. Methods: All adult patients with histologically confirmed hilar cholangiocarcinoma from 2003 to 2013 were evaluated for predictors of survival using demographic factors, laboratory data, symptoms and radiological characteristics at presentation. Results: A total of 116 patients were identified to have pathological diagnosis of hilar cholangiocarcinoma and were included in the analysis. Patients with a serum albumin level >3.0 g/dL ( P <  0.01), cancer antigen 19‐9 ≤200 U/mL ( P =  0.03), carcinoembryonic antigen ≤10 ìg/L ( P <  0.01) or patients without a history of cirrhosis ( P <  0.01) or diabetes ( P =  0.02) were associated with a greater length of overall survival. A serum albumin level >3.0 g/dL was identified as an independent predictor of overall survival (hazard ratio 0.31; 95% confidence interval 0.14–0.70) with a survival benefit of 44 weeks. Conclusion: This study was the largest analysis to date of prognostic factors in patients with hilar cholangiocarcinoma. A serum albumin level >3.0 g/dL conferred an independent survival advantage with a significantly greater length of survival.